2022
DOI: 10.1002/andp.202200026
|View full text |Cite
|
Sign up to set email alerts
|

Transparency and Enhancement in Fast and Slow Light in q‐Deformed Optomechanical System

Abstract: Nonclassical phenomena can be enhanced by introducing q-deformation in optomechanical systems. This motivates investigation of the optical response in a q-deformed linearly coupled optomechanical system. The system consists of two deformed cavities that are linearly coupled to the motion of mechanical mirrors, and the cavities are coupled to each other by transmission strength parameter. This study shows that compared to non-deformed cases, the deformed system exhibits more rapid phase transition at the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…In summary, q-calculus and q-deformed oscillators find applications in various domains of quantum science, from quantum field theory to quantum information theory, providing a powerful mathematical framework to describe and analyze systems in non-commutative settings. For more details, see [12][13][14][15].…”
Section: Introduction and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, q-calculus and q-deformed oscillators find applications in various domains of quantum science, from quantum field theory to quantum information theory, providing a powerful mathematical framework to describe and analyze systems in non-commutative settings. For more details, see [12][13][14][15].…”
Section: Introduction and Definitionsmentioning
confidence: 99%
“…This becomes particularly significant in situations involving systems subjected to extreme conditions, like those encountered in high-energy physics, the study of the early universe, or in the vicinity of black holes, where quantum gravity effects could play a substantial role. These mathematical methods provide a framework for probing and elucidating such phenomena; for more details, see [13][14][15]38].…”
mentioning
confidence: 99%
“…Deformed algebra is also used in open quantum systems to show the relationship between the efficiency of QHE and the amount of the non-Markovianity cycle processes [49]. One of the recent works showed that two linearly coupled q-deformed cavities could be tuned to provide enhancement of non-classical phenomena [50].…”
Section: Introductionmentioning
confidence: 99%